Representasi Pesan Moral dalam Film Remake A Business Proposal Versi Indonesia - Nurhalizah Halfiah Rezkina; Gibbran Prathisara (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
Film, as a mass communication medium, plays an important role in conveying moral values to society. The increasing number of remake films adapted from foreign works, including A Business Proposal Indonesian version, indicates a process of cultural adaptation that is interesting to study, particularly in the representation of moral messages. This study aims to analyze the representation of moral messages in the Indonesian version of A Business Proposal using the semiotic approach of Roland Barthes, as well as to identify the meanings contained in the film A Business Proposal Indonesian version. This research employed a qualitative research method with a semiotic approach. The primary data source was the film A Business Proposal Indonesian version, while secondary data were obtained from scientific literature such as books and journals related to film semiotics and communication studies. The determination of research data sources used purposive sampling techniques. Data collection was conducted through non-participant observation by repeatedly watching the film to identify relevant signs, as well as documentation in the form of recording dialogues, taking screenshots, and classifying scenes according to categories of moral messages. The data were then analyzed using Roland Barthes’ semiotic analysis model through several stages, namely denotative analysis, connotative analysis, and myth analysis. To ensure data validity, this study applied theory triangulation. The results of the study show that the film represents various moral values such as honesty, responsibility, professionalism, work ethics, family values, and integrity. These meanings are constructed through visual and verbal signs that reflect Indonesian cultural values. This study concludes that films not only function as entertainment media but also as a medium for moral education that is relevant to everyday life.